A new species of Psephenothrips (Thysanoptera:Phlaeothripidae) with one new record from India - Patidar, Abhishek; Singha, Devkant; Kumar, Vikas; Tyagi, Kaomud (Zootaxa, 2022)
Psephenothrips uttarakhandensis sp. n. is described and illustrated from India. Also, Neohydatothrips xestosternitus (Han & Cui) is newly recorded from India. The DNA barcode data using partial mitochondrial cytochrome c oxidase subunit I (mtCOI) from the holotype of the new species and one sequence of Neohydatothrips xestosternitus were generated and submitted to The Barcode of Life Data Systems (BOLD).